2017
DOI: 10.1097/md.0000000000008935
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between CT and MRI in the assessment of pulmonary embolism

Abstract: This meta-analysis demonstrates that MRI has better sensitivity and specificity in detecting subsegmental artery PE. MRI is a relatively better detection technique for PE. This conclusion is consistent with many published researches.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Patients with full or partial pneumonectomy, for example, will be challenged with MRI's longer apneic pauses. Vascular imaging with CT or MRI, in our experience and available literature, has almost identical clinical value when performed with contrast for both tumor invasion and pulmonary embolism caused by neoplasms 9 . For pulmonary embolism, CT is highly preferred than MRI as it is faster and the patient can receive critical care if needed by using normal hospital equipment.…”
Section: Comment On "Evaluation Of Pulmonary Nodules By Magnetic Reso...mentioning
confidence: 59%
“…Patients with full or partial pneumonectomy, for example, will be challenged with MRI's longer apneic pauses. Vascular imaging with CT or MRI, in our experience and available literature, has almost identical clinical value when performed with contrast for both tumor invasion and pulmonary embolism caused by neoplasms 9 . For pulmonary embolism, CT is highly preferred than MRI as it is faster and the patient can receive critical care if needed by using normal hospital equipment.…”
Section: Comment On "Evaluation Of Pulmonary Nodules By Magnetic Reso...mentioning
confidence: 59%
“…Currently, CTPA remains the gold standard for the diagnosis of PE as well as for PI and its complications [ 23 ]. However, results of a meta-analysis have suggested that the specificity and sensitivity of Magnetic Resonance Imaging (MRI) are slightly better than CTPA ones for the detection of acute PE [ 40 ]. Furthermore, MRI successfully identified PI on post-mortem examination [ 41 ].…”
Section: Possible Diagnostic Criteriamentioning
confidence: 99%
“…Furthermore, MRI successfully identified PI on post-mortem examination [ 41 ]. Therefore, MRI could be useful when CTPA is insufficient for the diagnosis of PI, thus helping in the differential diagnosis of alternative causes of parenchymal opacity [ 40 ]. Furthermore, MRI could discriminate the time of occurrence of PI.…”
Section: Possible Diagnostic Criteriamentioning
confidence: 99%